2016
DOI: 10.1186/s12887-016-0644-4
|View full text |Cite
|
Sign up to set email alerts
|

Health outcomes and the transition experience of HIV-infected adolescents after transfer to adult care in Québec, Canada

Abstract: BackgroundLittle is known on outcomes after transition to adult care among adolescents with perinatal HIV infection. Though there is data from other chronic pediatric diseases suggesting increased morbidity and mortality following transfer to adult care, this has not well been studied among the first wave of survivors of perinatal HIV infection. The primary objective of this study was to determine outcomes after transition to adult care among a cohort of HIV-infected adolescents in Québec, Canada. Secondary ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
63
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 25 publications
11
63
2
1
Order By: Relevance
“…While the prominence of age is not necessarily surprising, having been highlighted in other studies [34, 47], these findings do emphasize that tailored, age- and developmental appropriate transition should recognize the evolving capacity of adolescents [45]. This may have a gender-implication given that female adolescents, who generally mature earlier than their male counterparts were older in this study.…”
Section: Discussionsupporting
confidence: 61%
“…While the prominence of age is not necessarily surprising, having been highlighted in other studies [34, 47], these findings do emphasize that tailored, age- and developmental appropriate transition should recognize the evolving capacity of adolescents [45]. This may have a gender-implication given that female adolescents, who generally mature earlier than their male counterparts were older in this study.…”
Section: Discussionsupporting
confidence: 61%
“…In a study conducted among perinatally infected adolescent and youth in the UK, 16-20-year olds treated in adult care were found to have significantly higher mortality compared to 13-15-year olds treated in paediatric care (rate ratio 2.7; 95% CI 0.6-12.2) [17]. A recent study conducted in Canada reported that a quarter of transitioned patients were no longer engaged in care [55]. Although these data are from high-income settings, we may expect similar findings in low-resource settings where report of transition outcomes are less common [48,50].…”
Section: Discussionmentioning
confidence: 99%
“…However, in much of sub-Saharan Africa, where HIV care is implemented at primary healthcare clinics, there is no separation in paediatric and adult services and thus no need for transition of care [16]. Nevertheless, transition to adulthood still presents challenges for optimal HIV disease management as adolescent health needs evolve and autonomy for their own self care is necessary [17]. Many of these challenges are shared by both vertically and horizontally infected adolescents, although their disease progression and severity during adolescence may differ [18,19].…”
Section: Introductionmentioning
confidence: 99%